Image of Migrants and Refugees in Sweden in 2015 and the Following Years as Emerging from the Opinions of Political Elites and the Media Discourse - Wybranowski, Dariusz (Historia i Polityka, 2023)
The basis for the current analysis and the case-study method applied herein is provided by press reports, scholarly articles and books, both in the paper and online forms, containing the positions and statements by politicians from Sweden and elsewhere, the media community, public service officials, as well as average residents of Sweden who had encountered problems that resulted from the 2015 refugee crisis and the uncontrolled influx of migrants and refugees, especially those hailing from the Islamic world. Some of the research questions posed by the author are which Swedish political forces and circles supported this influx and which were against it, and how this was reflected in the political and media discourse. Other research questions concern the attitudes towards refugees and migrants presented by the country’s native residents and by persons of other origins who have lived there for a long time, as well as the factors influencing the media portrayal and the existing evaluation of events, in relation to the escalation of violence that occurred in some Swedish cities in the years 2016 and 2017. This issue is examined through an analysis of various statements made by residents of the Kingdom of Sweden: political figures, scholars, and ordinary people. The closing caesura is the year 2018 and the state of affairs after the parliamentary elections, in which the right-wing Sweden Democrats achieved a significant success. The analysis of the events of 2015–2018 as reflected in the media and political discourse, which is presented in the article, indicates how the massive influx of migrants and refugees has changed the sense of social security of the Swedes and what effects this “clash of civilisations” has already had and may have in the future.